2009
DOI: 10.1089/ten.tea.2008.0512
|View full text |Cite
|
Sign up to set email alerts
|

cAMP/PKA Signaling Inhibits Osteogenic Differentiation and Bone Formation in Rodent Models

Abstract: We previously demonstrated that cAMP-mediated protein kinase A (PKA) activation induces in vitro osteogenesis and in vivo bone formation by human mesenchymal stem cells (hMSCs). To analyze the species-specific response of this phenomenon and to translate our findings into a clinical trial, suitable animal models and cell lines are desirable. In this report, we assessed whether PKA plays a similar proosteogenic role played by two commonly used PKA activators-N6,2'-O-dibutyryl-cAMP (db-cAMP) and 8-bromo cAMP (8b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 58 publications
0
36
0
Order By: Relevance
“…These data may help in growing these cells ex vivo and explain some of the inconsistencies noted by investigators on cAMP signaling and growth of mesenchymal cells (47,(49)(50)(51). The present data are also helpful in understanding better the process of malignant transformation for which BSCs and other pluripotential cells are at risk (52).…”
Section: Discussionmentioning
confidence: 53%
“…These data may help in growing these cells ex vivo and explain some of the inconsistencies noted by investigators on cAMP signaling and growth of mesenchymal cells (47,(49)(50)(51). The present data are also helpful in understanding better the process of malignant transformation for which BSCs and other pluripotential cells are at risk (52).…”
Section: Discussionmentioning
confidence: 53%
“…For instance, a small molecule could be identified to activate signaling pathways that stimulate osteoblast-associated gene expression and matrix mineralization, which are processes associated with bone formation [199]. In fact, data from our group and others demonstrated that small molecule cyclic adenosine monophosphate (cAMP) analogs were able to induce in vitro and in vivo bone formation through the Protein Kinase A (PKA)/cAMP response element-binding protein (CREB) signaling mechanism [200][201][202][203]. It is also worth noting that the advances in high throughput screening technologies have yielded a large number of other osteoinductive small molecules in the past decade [176].…”
Section: Small Molecule Deliverymentioning
confidence: 99%
“…It has been shown that vascular smooth muscle cells and skeletal osteoblasts respond oppositely to the same stimuli, such as oxidized phospholipids and continuous activation of the PKA pathway (as in hyperparathyroidism) (3,24,(33)(34)(35)(36)(37), i.e. these factors promote osteoblastic differentiation of vascular cells but inhibit osteoblastic differentiation of bone cells.…”
Section: Table 2 Effect Of Pki On Tnf-␣ Induction Of Ranklmentioning
confidence: 99%